Analisis Pengendalian Internal Atas Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Pada PT. Bank Rakyat Indonesia (Persero) Tbk Kantor Cabang Depo - Arifialdi, Muhamad; Hanifan, Muhamad Zakie; ., Yudiana (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
Bank Rakyat Indonesia (BRI) is one of the largest government-owned bank in Indonesia. To be competitive in the banking world, the company should be able to improve services so that customers can feel satisfied and do not switch to another bank. All companies need cash for operations, but cash is the most sensitive assets against fraud so it needs a good internal control. By doing a good internal control companies can reduce their risk of loss from fraud which may be committed by employees. Internal control system applicable to the accounting information system is very useful to prevent and keep the things that are not desirable. Internal control system can also be used to check for errors that occurred so that it can be used to correct. The purpose of this study is to provide feedback to the company in order to improve security, especially through internal control of cash. This research was conducted with qualitative descriptive method in which the author direct observation to get a real picture of the internal control over the accounting information system cash receipts and disbursements. Results of research on the author to prove that internal controls had been inadequate because it has met the elements in internal control in accordance with the prevailing theories